Effects of Different N, P, and K Rates on the Growth and Cannabinoid Content of Industrial Hemp. Issue 1 (31st December 2023) - Wei, Xiuye; Zhou, Wei; Long, Songhua; Guo, Yuan; Qiu, Caisheng; Zhao, Xinlin; Wang, Yufu
ABSTRACT: As a key metabolite with high medical values in industrial hemp, cannabidiol (CBD) has been paid increasing attention. However, how nutrient supply affects the CBD content and yield of hemp remains unclear. Therefore, an aeroponic experiment with nine treatments (A1 A9) was conducted to evaluate the effects of different concentrations of nitrogen (N, at 4.0, 6.0, and 8.0 mmol L −1 ), phosphorus (P, at 1.0, 1.5, and 2.0 mmol L −1 ), and potassium (K, at 3.0, 4.0, and 5.0 mmol L −1 ) on the growth, CBD content, and biomass of hemp. Results showed that at A7 (N8P1K5) (N, P, K: 8, 1, 5 mmol L −1 ) markedly enhanced the dry weight of shoot and inflorescence with an increment of 208.7% and 435.7% respectively; the equivalent number of total CBD content in inflorescence was increased by 41.8%, and the CBD yield was increased by 7.0 times compared with A3 (N4P2K5). Correlation analysis revealed that N was positively related to the CBD yield, while P or K had a negligible effect on CBD yield. In conclusion, nutrient supply would dramatically influence the growth and CBD yield of hemp. Under the experimental conditions, A7 (N8P1K5) is the most suitable choice to cultivate hemp and achieve a higher CBD yield.